Mitochondrial 16S rRNA gene-based evolutionary divergence and molecular phylogeny of Barilius spp. (23rd July 2013) - Singh, Ajay Kumar; Kumar, Ravindra; Singh, Mahender; Mishra, Akhilesh Kumar; Chauhan, U. K.; Baisvar, Vishwamitra Singh; Verma, Rashmi; Nagpure, Naresh Sahebrao; Kushwaha, Basdeo
Abstract: Barilius is an important genus of fish family Cyprinidae, which comprises 22 species from Indian region. This study aimed to characterize five commonly occurring Bariline species, for example, Barilius bakeri. Barilius gatensis. Barilius vagra. Barilius bendelisis and Barilius tileo, across the country using partial mitochondrial 16 S rRNA gene, to estimate the order of inter- and intra-species divergence among these species and to establish phylogenetic and evolutionary relationships. The average inter-specific divergence was estimated as 7.10%. Intra-specific divergence of 0.20% and 0.10% was observed in B. gatensis and B. bendelisis that exhibited three and two haplotypes with 0.70 and 0.60 haplotype diversities, respectively. The NJ and MP phylogenetic trees were constructed using 16 S rRNA sequences along with sequences of the other five Indian cyprinid species retrieved from NCBI. Phylogenetic trees revealed five discrete branches each as a distinct species of the genus and exhibited identical phylogenetic relationship with other cyprinids. The study provided adequate information to distinguish the five Barilius species and indicated the suitability of 16S rRNA gene sequences in genetic divergence and phylogenetic studies.